UPAYA PENANGGULANGAN PROSTITUSI DI KALANGAN SISWA - Fransiska Novita Eleanora; Anggreany Haryani Putri (Abdi Bhara, 2022)
The increasingly widespread prostitution that occursnot only occurs among adults, but has also increased to childrenor among students, as well as contradicting the values and normsin society. It has a negative impact on sociological, educational,economic, health and urban planning aspects. And also there arepreventive, repressive and curative countermeasures. Thepurpose of this activity is to find out the impact andcountermeasures, so as to avoid and not become victims of thepractice of prostitution. As well as the existence of legalprotection for victims of prostitution such as compensation,medical and social rehabilitation. The method of this activity iscarried out through stages, namely a) counseling by thepresenter, b) question and answer session from participants tothe presenter, c) evaluation related to the activity material thathas been delivered. The results of this activity 1) already knowand understand the impact and prevention of prostitution 2)understand the legal rules and sanctions related to prostitutionboth as perpetrators and victims. Activities in community servicecan be carried out in a sustainable manner for students and thecommunity.